Electromyographic analysis of the arm muscles in back support exercises - Guazzelli Filho, Joffre [UNESP]; Dias, G. A R; Rodrigues, J. A.; Gonçalves, M. [UNESP]; Büll, Marilena Longo [UNESP] (My University, 2007)
This study aims at quantifying through electromyography the actions of the biceps brachii-BB (long head), tríceps brachii- TB (long head) and deltoideus-DA (clavicular portion) muscles, during the going (G) and return (R) phases in back support exercises. Surface electrodes were placed at the muscles, according to DELAGI (1981). It was used a specific software and a AID plate to take the signals. After being collected, the records were processed resulting in efficient values (RMS), were normalized by maximum isometric contraction (MVIC=100%) and statistically analysed using the Friedman, DSM and Wilcox non-parametric tests. All the muscles presented electromyographic activity of the movements. The triceps brachii was the muscle with higher activity in both phases of the movement. It was concluded that the exercise is indicated for the arm muscle strength development.
Keywords: Biceps brachii; Deltoideus; Electromyography; Exercise; Triceps brachii; adolescent; adult; arm muscle; biceps brachii muscle; controlled study; deltoid muscle; electromyography; exercise physiology; Friedman test; human; human experiment; male; muscle exercise; muscle isometric contraction; muscle strength; nonparametric test; normal human; triceps brachii muscle; Adolescent; Adult; Arm; Humans; Male; Muscle Contraction; Muscle, Skeletal; Reference Values